High/Positive Expression of 5-Fluorouracil Metabolic Enzymes Predicts Better Response to S-1 in Patients with Gastric Cancer: A Meta-Analysis. Issue 2 (April 2016) - Wang, Dan; Yu, Xuejun; Wang, Xiuwen
Purpose: To provide an assessment by meta-analysis of the relationship between the expression variations of 5-fluorouracil metabolic enzymes and clinical outcomes in patients with gastric cancer treated with S-1. Method: Databases were searched electronically from inception to April 19 th, 2015. Studies in gastric cancer patients treated with S-1 investigating the expression variations of 5-fluorouracil metabolic enzymes were included after having been identified systematically. Pooled odds ratios (OR) for the objective response rate (ORR) and median survival ratio were calculated using the Review Manager 5.3 and Stata 12.0 software separately. Results: A total of 555 patients in 10 studies met our inclusion criteria. There was a significant difference in ORR between patients with high/+ and low/- expression of orotate phosphoribosyl transferase (OPRT) (OR = 8.06; 95% CI, 4.06-16.02; p<0.001) and dihydropyrimidine dehydrogenase (DPD) (OR = 1.95; 95% CI, 1.21-3.13; p = 0.006). There was no significant difference in ORR between different expression levels of thymidylate synthase (TS) and thymidine phosphorylase (TP). Although patients with low/- TS expression, low/- TP expression and high/+ DPD expression showed a trend towards longer survival, no statistical significance was found. The median OS was significantly longer in patients with high/+ expression of OPRT (p = 0.076). Conclusions: OPRT and DPD expression can be treated as a potential predictive biomarker for S-1 response in gastric cancer patients. Further investigation is warranted.